Network pharmacology and molecular docking of cucurbitane-type triterpenoids from Momordica charantia against psoriasis-associated targets - Ahmad Bayu Satriawan; Sarmoko; Tantri Liris Nareswari; Nisa Yulianti Suprahman; Muh Fajar Fauzi; I Gede Raditya Purwanata (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2026)
Psoriasis is a chronic immune-mediated inflammatory skin disorder characterized by keratinocyte hyperproliferation, persistent inflammation, dysregulated apoptosis, and tissue remodeling. Momordica charantia has attracted attention as a potential anti-psoriatic herbal candidate; however, the molecular basis of its bioactive metabolites remains insufficiently understood. This study investigated the anti-psoriatic potential of cucurbitane-type triterpenoids from M. charantia using integrated network pharmacology and molecular docking. Of 192 secondary metabolites, 50 passed pharmacokinetic and toxicity screening, yielding 347 predicted human targets, of which 159 overlapped with 3,383 psoriasis-associated genes. Key hub genes identified by protein-protein interaction and topological analyses included AKT1, TNF, EGFR, STAT3, IL1B, CASP3, MMP9, HIF1A, and ESR1, with enriched biological processes related to oxidative stress, lipid and hormonal responses, and intracellular receptor signaling. Molecular docking of five cucurbitane-type triterpenoids against four validated hub proteins demonstrated consistently favorable predicted binding affinities for AKT1 via its allosteric pocket, as well as for EGFR and IL1B. Karavilagenin A showed the most favorable binding energy against AKT1, momordicin I against EGFR and IL1B, and cucurbitacin B demonstrated favorable profiles across multiple targets. These findings suggest that M. charantia may influence psoriasis-related biology through multi-target mechanisms, providing a basis for further experimental validation.